On the Role of Formers in Violent Extremism Tertiary Prevention Programs - McBride, Megan (Journal for deradicalization, 2025)
The question of what roles, if any, former extremists can or should play in PVE efforts is one that has received increased attention in recent years. This article contributes to that conversation by collecting input from preventing violent extremism (PVE) experts we brought together in June 2023 for a full-day workshop. More specifically, our research team recruited a group of 12 US-based PVE experts—all of whom had some experience working with Formers extremists—to participate in a structured discussion about the protection, supervision, and use of formers in PVE work. The issues raised by the experts fell into four broad categories: the roles that formers have played in US PVE, the qualifications and training formers should have, the effectiveness of formers in facilitating PVE, and the ethics of their involvement. Broadly speaking, we find that PVE practitioners’ support for the involvement of formers in PVE activities is heavily caveated by a range of concerns related to qualifications, training, and scope of work. Additionally, a review of the literature finds minimal support for the involvement of formers in PVE, and raises a range of ethical issues that the field has not yet fully addressed. Acknowledgements This project was made possible by funding and support from the National Institute of Justice (Evaluability assessment and development of psychological and behavioral health approaches to prevent terrorism and facilitate reintegration of violent extremists; Award Number 15PNIJ-21-GG-02727-DOMR). The content of this manuscript as well as the views expressed therein are solely those of the authors and do not necessarily represent the official views of NIJ, nor does mention of trade names, commercial practices, or organizations imply endorsement by the U.S. government.